Implementation of blended learning model in the ISMUBA curriculum during Covid-19 Pandemic - Aulia Rohmana (Journal of Islamic Education and Innovation, 2022)
The learning model during the pandemic has changed along with the prohibition of face-to-face to avoid transmission of the Corona virus. This has led to various adjustments by teachers and students to keep the curriculum running, including the ISMUBA curriculum. This study aims to describe the implementation of blended learning in the ISMUBA curriculum as a form of adjustment during a pandemic. Since the implementation of learning from home, the blended learning method is the right method to be used in this day. Blended learning is a combination of face-to-face learning and learning that utilizes affirmation technology in its implementation. This study used a qualitative descriptive method, all data in this study were obtained through a series of interviews with informant. The informant is ISMUBA teacher. The results showed that blended learning can be used as an alternative learning strategy in the ISMUBA curriculum.